2009
DOI: 10.1063/1.3079795
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between coupling and anisotropy fields in exchange-biased bilayers

Abstract: In the framework of models that assume planar domain wall formed at the antiferromagnetic part of the interface of exchange-biased bilayers, one cannot distinguish between the cases of high or low ratios between the coupling and the antiferromagnet's anisotropy fields by using hysteresis loop measurement, ferromagnetic resonance, anisotropic magnetoresistance, or ac susceptibility techniques applied on one and the same sample. The analysis of the experimental data obtained on a series of FeMn/Co films indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 51 publications
2
13
1
Order By: Relevance
“…13 At t AF ∼ = 40Å, where the EB anisotropy starts to establish, H RA reaches its maximum value. In region II, opposite trends for H E and H RA indicate that changes at the FM-AF interface occur, 15 with the increase of H E produced by the increasing number of the stable AF grains at the expense of a reduction in the number of the rotatable ones. In region III, for t AF > 80Å, both H E and H RA attain their saturation values because most of the IrMn grains at the interface are magnetically stable.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…13 At t AF ∼ = 40Å, where the EB anisotropy starts to establish, H RA reaches its maximum value. In region II, opposite trends for H E and H RA indicate that changes at the FM-AF interface occur, 15 with the increase of H E produced by the increasing number of the stable AF grains at the expense of a reduction in the number of the rotatable ones. In region III, for t AF > 80Å, both H E and H RA attain their saturation values because most of the IrMn grains at the interface are magnetically stable.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, there exists a critical thickness of the AF below which the EB vanishes. 15,16 In addition to this, it has been observed that the coercivity and the rotatable anisotropy field show maximum values for different AF layer thicknesses. 15,[17][18][19][20][21] FM resonance has been shown to be one of the most successful techniques used to determine the values of the effective fields associated with the magnetic anisotropies in FM thin films and multilayers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it is found that the PDW model will give the same exchange bias field as the RAF model if the domain-wall energy is much larger than the interfacial exchange-coupling energy. 26,30,33 Consequently, PDW model seems to be more fundamental or flexible than RAF model, and that is why we choose PDW model to discuss the ADEB in present paper.…”
Section: Introductionmentioning
confidence: 99%
“…27,28,[42][43][44][45][46] On the basis of the PDW model, Geshev et al have performed a series of researches on the exchange bias effect. [29][30][31][32][33][34][35][36][37] The distribution of the AFM axis, the enhancement of the coercivity, the dependence of the exchange bias on the measurement techniques, temperature, and the rotatable anisotropy have been discussed systematically in their works. These studies suggest that only using the PDW model, the magnetic behaviors of these exchange-biased systems can be well understood.…”
Section: Introductionmentioning
confidence: 99%